Implementation of competency-and-conservation-based curriculum to improve graduatesâ quality to be competent and conservation-minded - Asrori, Asrori (Dinamika Pendidikan, 2016)
This study was aimed to analyze how the implementation of Kurikulum Berbasis Kompetensi dan Konservasi or Competency-and-Conservation-Based Curriculum (KBKK) improves the quality of graduates from Faculty of Economics of Universitas Negeri Semarang (UNNES). The goal of this study was to provide information and policy recommendations to improve the quality of graduates based on behavior lectures. The respondents of this research were lecturers of Faculty of Economics. Research data were collected using questionnaires to dig up information on the implementation of KBKK, lecturersâ ability and commitment to implement KBKK. Descriptive statistics and inferential statistical multiple linear regression were employed to analyze data. This study provided empirical support that lecturersâ ability and commitment positively contributed to the implementation of KBKK to improve the quality of graduates to be competent and conservation-minded. This study also proved that while lecturersâ ability and commitment play an important role, their commitment does not affect the implementation KBKK. Based on the results of this study, it is recommended that lecturersâ ability to implement KBKK needs to be improved. Workshops and training should be given to lecturers to help them create learning apparatus such as syllabus, lesson plans and teaching materials, as well as the evaluation of KBKK.Penelitian ini bertujuan untuk menganalisis bagaimana penerapan kurikulum berbasis kompetensi dan konservasi (KBKK) mampu meningkatkan kualitas lulusan Fakultas Ekonomi universitas negeri Semarang. Urgensi dari penelitian ini adalah untuk memeberikan informasi dan rekomendasi kebijakan untuk meningkatkankualitas lulusan melalui kompetensi dosen. Penelitian ini dilakukan terhadap dosen dilingkungan Fakultas Ekonomi. Pengumpulan data dilakukan dengan mengunakan angket, untuk menggali informasi penerapan Kurikulum berbasis Kompetensi dan onservasi (KBKK), kemampuan dosen, dan komitmenya dalam penerapan kurikulum berbasis kompetensi dan konservasi. Analisis data dilakukan dengan menggunakan deskriptif statistik dan statistik inferensial menggunakan regresi berganda.